Association between maternal antidepressant use during pregnancy and autism spectrum disorder: an updated meta-analysis - Xi-Hong Zhou; Yong-Jiang Li; Jian-Jun Ou; Ya-Min Li (Molecular Autism, 2018)
Abstract Studies have investigated the risk of autism spectrum disorder (ASD) in children exposed in utero to antidepressant, with inconsistent results. Given the substantial public health implications on this topic, here, we presented an updated meta-analysis of the association between maternal antidepressant use during pregnancy and ASD. Cochrane Library, EMBASE, PsycINFO, and PubMed databases were systematically searched. A random effects model was used to pool the adjusted relative risk (RR) for cohort studies and the adjusted odds ratio (OR) for case-control studies as well as their corresponding 95% confidence intervals (CIs). Meta-analysis restricted to sibling studies was also conducted. Publication bias was systematically assessed. Fourteen studies were identified (eight cohort studies and six case-control studies). Pooled adjusted RR for cohort studies (n = 2,839,980) was 1.13 (0.93–1.39) showed a non-significant association; while two studies were potentially missing from the test of publication bias, filled estimates also showed a non-significant association (filled RR 0.97, 95% CI 0.79–1.19). Pooled OR was 1.51 (1.15–1.99) for case-control studies (n = 117,737) showed a significant association; two studies were potentially missing; however, the filled estimates suggested a non-significant association (filled OR 1.26, 95% CI 0.98–1.62). Analyses restricted to sibling studies also showed a non-significant association (RR 0.99, 95% CI 0.81–1.22). In summary, we did not evidence a significant association between maternal antidepressant use during pregnancy and ASD.